Usage of Eucalyptus globulus bark as a raw material for natural antioxidant and fuel source - Pasakorn Jutakridsada (2018)
© 2016, Springer-Verlag Berlin Heidelberg. The concept of clean technology was applied in the traditional process of using Eucalyptus globulus bark as fuel in the pulp and paper industry. The bark was investigated for its potential as a source of antioxidants by the solid–liquid extraction process before being used as fuel source. An experiment was set up to determine its antioxidant capacity and heating value. Volatile components of the extracts were also identified and analyzed by gas chromatography–mass spectrometry. The experimental results suggested that ethanol extraction solution at a ratio of 1:20 yielded the highest content of phenolic compounds (674.19 mg of gallic acid/l) and antioxidant capacity (30.53 ± 1.76 mg/l). We also examined and compared the fuel properties of extracted and unextracted bark, and it was found that the fuel properties of extracted and unextracted bark showed no significant difference. These findings suggested that the bark can be put to a better use by extracting the compounds before being ultimately used as fuel source in the traditional process. This might lead to an alternative process for the pulp and paper industry in which the standard process is maintained to obtain the desired products, with the additional extraction process to obtain high-value compounds.